Prevalence of Shovel-Shaped in Patients of the Faculty of Dentistry of the University of Costa Rica. A Pilot Study - Bolaños DDS, Violeta (Odovtos - International Journal of Dental Sciences, 2015)
The objective of this research was to determine the prevalence of shovel shaped teeth in a group of patients between 4 and 14 years old. A descriptive transversal clinical study was done by observing the patients of the Odontopediatrics Clinic, during March 2013 and December 2014. The Statistical Logistic Regression Method was used to study the prevalence of the abnormality by gender. The results showed that 96 patients presented shovel shaped teeth, which corresponds to 32% of the population; from which 13% were boys and 19% were girls. Concluding that the prevalence of shovel shaped teeth with a 95% of confidentiality was of 32%.